Analisis Miskonsepsi Siswa SMP pada Materi Konsep Suhu dan Kalor - Cindy Dwi Cahyaningtyas; Elisa Fatma; Pingkan Aprileni Memorika Rianto; Ulin Nuha; Sri Wahyuni; Firdha Yusmar (Peneliti.net, 2023)
Students experience misconceptions when the knowledge they build is not in accordance with scientific concepts. This research investigates misconceptions about heat and temperature. The purpose of this research is to understand the importance of understanding the concepts that students must have, so as to reduce the quantity of misconceptions obtained from learning experiences or references from books or journals that are not quite right. This study uses library research methods. The results of the analysis of various literatures state that there are misconceptions about temperature and heat using test instrument research in the form of three-tier multiple choice questions. The results of the study showed that the correct answer was 35.13%, and the average student misconception was 69% for temperature material and 63.79% for heat material. Research from other literature states that students' misconceptions occur in the concept of thermal equilibrium. Factors that cause misconceptions can be seen based on the analysis of students' answers, besides that it can be seen from the weak mastery of physics material. Based on the data analysis, it can be concluded that the importance of understanding the concept that students must have so that it is easier for students to understand the concept of the next material.